Childfree Is Not A Disgrace For Women: Harmonizing the Stoicism-Mubadalah Paradigm in Fighting Stigma and Gender Discrimination - Maliki, Ibnu Akbar; Zhafira, Annisa Ranah (JOURNAL OF ISLAMIC AND LAW STUDIES, 2025)
Women's decision not to have children (childfree) is always labeled as an act that violates social norms. This is further exacerbated by patriarchal religious interpretations that limit women's roles to the domestic sphere. This social construct often leads to discrimination against childfree women and ignores their right to determine their own happiness in life. This article analyzes the childfree choice as a manifestation of women's pursuit of happiness and autonomy through the lens of Stoic philosophy and the Mubadalah paradigm of reciprocity. This descriptive qualitative study uses literature review with primary data from the book “Qira'ah Mubadalah” by Faqihuddin Abdul Kodir and “Filosofi Teras” by Henri Manampiring, as well as secondary data from various relevant literature. Data was collected through documentation techniques and analyzed using content analysis. The results of the study show that Stoicism and Mubadalah create a strong paradigm to counter stigma and gender discrimination against childfree women. Despite originating from different traditions, both offer significant support for childfree women. Stoicism empowers individuals to find happiness from within, through control over thoughts and internal responses to external pressures, including social stigma. On the other hand, Mubadalah provides a strong theological foundation for deconstructing patriarchal narratives in religious interpretations that limit women's roles to reproductive functions. Both approaches emphasize individual freedom in determining one's life path, focusing on internal quality of life, and recognizing happiness as a dynamic process. Ultimately, this study affirms that discrimination against childfree women is an act that is inconsistent with human values and inclusive religious teachings, and therefore needs to be addressed with a more just and equitable understanding